Patterns in Student Assignment to Elementary School Classrooms - Bosworth, Ryan; Li, Hao (Education Policy Analysis Archives, 2013)
In an effort to better understand aggregate patterns in the way elementary school students are assigned to classes, we conduct a careful analysis of observed classroom assignment outcomes in the 5th grade in North Carolina elementary schools. First, we model the probability that a pair of students are classmates as a function of the characteristics of that pair of students. This novel methodological technique enables us to directly observe the degree to which actual assignment patterns differ from what might be expected under random assignment for a wide variety of student characteristics. Second, we analyze patterns in classroom assignment and discuss the implications of these patterns. We show that classroom assignments tend to deviate from random assignment in a way that tends to group similar students and that these deviations tend to be greatly magnified in Magnet schools. Importantly, we find evidence that administrators sort students based on attributes not normally observable by researchers. These findings have important implications for researchers using value-added modeling (VAM) techniques. Finally, we find that classroom assignment patterns are generally stable across the racial, income, and geographic characteristics of schools.